1996
DOI: 10.1037/0278-6133.15.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Time course of natural killer cell activity and lymphocyte proliferation in response to two acute stressors in healthy men.

Abstract: To clarify the time course of immune system activity during and after acute stressor exposure, this study collected immune measures from 31 men at 6 times (before, during, and after 2 common laboratory stressors; mental arithmetic with harassment or a cold pressor task). The 6-min stressor period was associated with increased self-report of pain and distress in both stressor groups and with increased systolic and diastolic blood pressure and heart rate in the mental arithmetic group. Increased natural killer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
2
26
2
Order By: Relevance
“…Previously, in a study of nasal obstruction model rats, an acute elevation of glucocorticoids, a stress hormone, and decrease in body weight was confirmed (19). In the present study, the mild hypoxia group demonstrated reduced body weight at D1, increase under acute stress (21). In addition, in a report by Oya et al, that evaluated the immune function of animals exposed to acute restraint stress, it was reported that the ratio of innate immunity including the NK cells was enhanced 24 hours after the initiation of the study (22).…”
Section: Nk Cell Ratio In the Splenic Lymphocytessupporting
confidence: 58%
See 1 more Smart Citation
“…Previously, in a study of nasal obstruction model rats, an acute elevation of glucocorticoids, a stress hormone, and decrease in body weight was confirmed (19). In the present study, the mild hypoxia group demonstrated reduced body weight at D1, increase under acute stress (21). In addition, in a report by Oya et al, that evaluated the immune function of animals exposed to acute restraint stress, it was reported that the ratio of innate immunity including the NK cells was enhanced 24 hours after the initiation of the study (22).…”
Section: Nk Cell Ratio In the Splenic Lymphocytessupporting
confidence: 58%
“…In the D7, D14, and D21 groups, the NK cell ratio in the mild hypoxia groups was significantly lower than that of the control groups. It was previously reported that long-term stress reduces immunity by the HPA axis (21). In addition, the long-term activation of the physiological stress response can push animals into allostatic overload, which in turn may lead to a suppressed immune function (32).…”
Section: Nk Cell Ratio In the Splenic Lymphocytesmentioning
confidence: 99%
“…It would seem equally important to study responses to passive stressors, such as the cold pressor test, which are characterized by alpha-adrenergic activation~e.g., increased peripheral resistance!. Few studies have investigated the cellular immune response to passive stress tasks~Chi, Neumann, MotaMarquez, & Dubberley, 1993;Delahanty et al, 1996;Eller, 1998;Zakowski, Cohen, Hall, Wollman, & Baum, 1994!. Only two reported immune cell counts, both in response to cold pressor. Chi et al found changes in the percentage of lymphocytes and neutrophils, although the direction of the change varied according to the resting baseline used.…”
mentioning
confidence: 99%
“…In contrast, studies involving human subjects have demonstrated an increase in NK cell activity in response to local or generalized cold exposure (26). Delahanty et al IL-6 response.…”
Section: Effects Of Passive Heating and Moderate Exercise (With And Wmentioning
confidence: 98%